Occurrence of antibiotic resistant Salmonella and Campylobacter in wild birds - Mustaffa, Siti Sajidah; Abdul Aziz, Saleha; Abu, Jalila (Veterinary Association Malaysia, 2014)
Salmonella and Campylobacter are well recognised as important zoonotic foodborne pathogens. This study was undertaken to detect the occurrence of Salmonella and Campylobacter in a population of wild birds and to determine the antibiotic susceptibility of the isolates. A total of 68 fresh faecal samples were collected from wild birds in four areas (Bangi, Kepong, and two areas in Serdang). One (1.47%) faecal sample was positive for Salmonella spp. from a pigeon in Kepong and the isolate was resistant to erythromycin and tetracycline. Six (8.82%) faecal samples were positive for Campylobacter spp, three (50%) were from pigeons in Serdang and another three (50%) were pigeons from Kepong. All isolates were identified as Campylobacter jejuni and were resistant to trimethoprim-sulfamethoxazole (100%), followed by cefotaxime (83.3%), tetracycline (33.3%) and ampicillin (16.7%). The presence of antibiotic resistant Salmonella spp. and Campylobacter spp. in wild birds poses a public health risk because they may transmit these antibiotic resistant pathogens to farm animals and spread them in the environment